2006
DOI: 10.1007/s00439-006-0205-2
|View full text |Cite
|
Sign up to set email alerts
|

A maternal hypomethylation syndrome presenting as transient neonatal diabetes mellitus

Abstract: The expression of imprinted genes is mediated by allele-specific epigenetic modification of genomic DNA and chromatin, including parent of origin-specific DNA methylation. Dysregulation of these genes causes a range of disorders affecting pre- and post-natal growth and neurological function. We investigated a cohort of 12 patients with transient neonatal diabetes whose disease was caused by loss of maternal methylation at the TNDM locus. We found that six of these patients showed a spectrum of methylation loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
104
2
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 33 publications
(35 reference statements)
9
104
2
4
Order By: Relevance
“…These findings underline the lower birthweight and earlier presentation in 6q24 TNDM that is caused by potassium channel mutations (<1st vs 12th centile, and <1 week vs 4 weeks, respectively). However, the relatively low birthweight previously reported in duplication patients [8] was not supported by this study. While birthweight (adjusted for gestation) was normally distributed, the ages of presentation and remission of diabetes were markedly skewed, with modes at 1 day and 2 months, but means of 8 days and 4.5 months.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings underline the lower birthweight and earlier presentation in 6q24 TNDM that is caused by potassium channel mutations (<1st vs 12th centile, and <1 week vs 4 weeks, respectively). However, the relatively low birthweight previously reported in duplication patients [8] was not supported by this study. While birthweight (adjusted for gestation) was normally distributed, the ages of presentation and remission of diabetes were markedly skewed, with modes at 1 day and 2 months, but means of 8 days and 4.5 months.…”
Section: Discussioncontrasting
confidence: 99%
“…1 Similar dual LOM had previously been demonstrated in two patients by Arima et al 2 Subsequently, we showed that 6 out of 12 anonymised TNDM patients with LOM at TNDM DMR (6q24) in addition had a diverse spectrum of maternal hypomethylation at multiple imprinted loci including KCNQ1OT1 (11p15.5), and we suggested the existence of a maternal hypomethylation syndrome. 3 A similar spectrum of multiple maternal hypomethylation was found by Rossignol et al, 4 in 10 out of 40 LOM BWS patients.…”
Section: Introductionsupporting
confidence: 67%
“…[2][3][4][5][6][7][8][9][10][11][12], PEG1/MEST (7q32), KCNQ1OT1 and H19 (both 11p15.5), DLK1 (14q32), SNRPN (15q11-12), PEG3 (19q13), and NESPAS (20q13) by methylation-specific PCR (MS-PCR) following bisulphite treatment, as previously described. 1,3,5 Primer sequences for NESPAS were derived from Williamson et al 6 Aberrant results were confirmed by either pyrosequencing 7 or MS-PCR with another primer set. Control data were drawn from previous publications, 1,3 with supplementary MS-PCR at some loci to obtain an epigenotype of all 120 anonymised normal controls at all the loci.…”
Section: Laboratory Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 A subset of BWS patients with hypomethylation at the KCNQ1OT1 ICR (IC2 defect, ICD2) have loss of methylation at other imprinted loci. 9 Hypomethylation of multiple maternally methylated ICRs including KCNQ1OT1 has also been demonstrated in cases of transient neonatal diabetes 10,11 (TND, OMIM 601410). TND is a disease characterised by intrauterine growth retardation and transient hyperglycaemia that results from dysregulation of the imprinted growth inhibitor and antiapoptotic PLAGL1 (ZAC) gene located at chromosome 6q24.…”
Section: Introductionmentioning
confidence: 99%